Air renewal in classrooms with split air conditioning - Xavier, Eric Loque Magalhães; Pagel, Erica Coelho; Martins, Ramon Silva (Technical and Scientific Journal Green Cities, 2024)
The study evaluates the air changes per hour in a classroom air-conditioned with split-type air conditioning, using the concentration of carbon dioxide (CO₂) as an indicator of ventilation. The objective is to verify the compliance of this rate with current standards and determine the effectiveness of ventilation in controlling indoor air quality. The experiment was carried out at a technical school located in the city of Serra, Espírito Santo, during the winter of 2024. CO₂ levels, temperature and relative humidity were monitored using the HOBO Data Logger MX1102A monitor. The results indicate that the air changes per hour was below the minimum levels recommended by ABNT NBR 16.401-3, ASHRAE 62.1 and EN 13779 standards, especially with windows and doors closed. CO₂ concentrations exceeded the limits established by the standards, indicating compromised air quality and potential risks to the health of occupants. It was found that natural ventilation, through opening windows and doors, has the potential to significantly increase the air changes per hour. It is concluded that an individualized analysis of ventilation in classrooms is essential, adjusting the air changes per hour to the specific characteristics of each environment to ensure compliance with standards and the preservation of the health of occupants.
Keywords: Indoor air quality; Air changes per hour; air conditioning; Classroom